2014
DOI: 10.1001/jamapediatrics.2014.1609
|View full text |Cite
|
Sign up to set email alerts
|

Placebo Effect in the Treatment of Acute Cough in Infants and Toddlers

Abstract: clinicaltrials.gov Identifier: NCT01721395.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 21 publications
0
12
0
3
Order By: Relevance
“…In addition to the common cold, bronchitis, chronic obstructive pulmonary disease (COPD), cystic fibrosis, and asthma can also generate coughing (Trebbia et al 2005 ;Hargreave & Parameswaran 2006 ;Serisier et al 2009 ;Bucca et al 2010 ). Coughing is present in many diseases and is one of the most common reasons that patients seek medical services (Iyer & Lim 2013 ;Paul et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the common cold, bronchitis, chronic obstructive pulmonary disease (COPD), cystic fibrosis, and asthma can also generate coughing (Trebbia et al 2005 ;Hargreave & Parameswaran 2006 ;Serisier et al 2009 ;Bucca et al 2010 ). Coughing is present in many diseases and is one of the most common reasons that patients seek medical services (Iyer & Lim 2013 ;Paul et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Когда я впервые увидел статью о том, что ложка меда на ночь уменьшает кашель ребенка так же (если не лучше), как и противокашлевые средства [1], я понял автора, измученного бесконечными жалобами родителей на кашель у их ребенка. Ведь эти больные занимают до 25% времени приема практикующего педиатра, вынужденного, как испорченная пластинка на патефоне, без конца повторять сентенции о связи кашля с состоянием носоглотки, о разных видах кашля, о нецелесообразности борьбы с кашлем как таковым [2]. Когда я начинал свою врачебную деятельность, еще можно было выписывать кодеин, но уже тогда необходимость его назначения подвергалась сомнению, поэтому использовали в основном микстуры с алтеем или нашатырно-анисовые капли.…”
unclassified
“…Honey could be effective and safe, though it should be used with caution for children less than one year old, since, because of the immaturity of their intestinal mucosa, they are more susceptible to botulism spores that could be contained in the honey [50]. A trial published in 2014 also showed a significant effect on cough scores of placebo (grape juice) versus a pure ‘wait and see’ approach [51]. …”
Section: Resultsmentioning
confidence: 99%
“…Without red flags or signs of common disease, in children suffering from isolated non-specific cough, it is not recommended and does not seem beneficial to provide empirical anti-asthma [51-53] or anti-reflux treatments [25], or treatment for allergic rhinitis [17]. …”
Section: Resultsmentioning
confidence: 99%